Medicinally Wild Edible Vegetables And Fruits Of Kurdistan Region Of Iraq (Applied Biological Research, 2023)
As medicine, wild edible plants have a significant socioeconomic impact. The  connection between food and health is historical, as customers increasingly want  healthy, flavourful, and natural functional foods. Knowledge of such foods is  primarily transferred through the contributions of household members. Because  the traditions of using wild edible plants as food and medicine are at risk of  extinction around the world. In this study, snowball sampling was adopted.  Thirty-seven (37) wild edible plant species from 17 families, with Fabaceae  (18.9%) being the most dominant one, followed by Apiaceae (16.2%),  Anacardiaceae, Moraceae and Malvaceae 8.1%, respectively, mostly used for a  range of medicinal purposes. Leaves and fruits accounted for 26.42%,  respectively. Majority of the respondents in this survey were from age 41 to 50  (38.2%). There is a considerable variety of wild vegetables and fruits that are  used medicinally, and there is also well-maintained community knowledge about  how to use wild fruits and veggies plants for people of all ages. The results of this  investigation will also provide locals with a useful starting point for choosing  significant wild foods for medicinal uses.
Keywords: Ethno-medicinal plants; fruits; traditional knowledge; vegetables